A PROMINENT RUSSIA ONCOLOGIST BORIS NIKOLAEVICH ZYRYANOV (1940–2002) - E. L. Choinzonov; S. A. Nekrylov (Сибирский онкологический журнал)
The article presents a biographical sketch of B.N. Zyryanov, a prominent Russian oncologist, Director of Tomsk Cancer Research Institute in the period from 1987 to 2002, Academician of the Russian Academy of Medical Sciences, Professor.